SELECT a.日期, a.物资ID, a.名称, a.期初, a.收料, (select sum(b.收料) from 基础查询 as b where b.物资ID=a.物资ID and b.日期<=a.日期) AS 收料累计, a.发料, (select sum(b.发料) from 基础查询 as b where b.物资ID=a.物资ID and b.日期<=a.日期) AS 发料累计
FROM 基础查询 AS a;
SELECT a.日期, a.物资ID, a.名称, 期末+发料-收料 AS 期初, a.收料, a.发料, (select sum(b.期初+b.收料-b.发料) from 基础查询 as b where b.物资ID=a.物资ID and b.日期<=a.日期) AS 期末
FROM 基础查询 AS a;
SELECT (select count(*) from 基础查询 as b where b.物资ID=a.物资ID and b.日期<=a.日期) AS 序号, a.日期, a.物资ID, a.名称, 期末+发料-收料 AS 期初, a.收料, a.发料, (select sum(b.期初+b.收料-b.发料) from 基础查询 as b where b.物资ID=a.物资ID and b.日期<=a.日期) AS 期末
FROM 基础查询 AS a;
SELECT a.物资ID, a.名称, a.日期, a.日期-(select last(b.日期) as 日期1 from 基础查询2 as b where b.物资ID=a.物资ID and b.日期<a.日期) AS 收料周期, a.收料, a.收料-(select last(b.收料) as 收料1 from 基础查询2 as b where b.物资ID=a.物资ID and b.日期<a.日期) AS 收料变动, Round(收料变动/a.收料,4) AS 变动幅度
FROM 基础查询2 AS a;